Volume 2: 31st Computers and Information in Engineering Conference, Parts a and B 2011
DOI: 10.1115/detc2011-48452
|View full text |Cite
|
Sign up to set email alerts
|

Using GPU-Based Computing to Solve Large Sparse Systems of Linear Equations

Abstract: Often thought of as tools for image rendering or data visualization, graphics processing units (GPU) are becoming increasingly popular in the areas of scientific computing due to their low cost massively parallel architecture. With the introduction of CUDA C by NVIDIA and CUDA enabled GPUs, the ability to perform general purpose computations without the need to utilize shading languages is now possible. One such application that benefits from the capabilities provided by NVIDIA hardware is computational contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Kiss et al 15 demonstrated the utilization of GPUs for the element-by-element (EbE) FEM. Carrigan et al 16 used GPU-based computing to solve large sparse systems of linear equations. But almost no scholars apply it into intelligent optimization algorithm to solve the problem of optimization arrangement on mistuned blades.…”
Section: Introductionmentioning
confidence: 99%
“…Kiss et al 15 demonstrated the utilization of GPUs for the element-by-element (EbE) FEM. Carrigan et al 16 used GPU-based computing to solve large sparse systems of linear equations. But almost no scholars apply it into intelligent optimization algorithm to solve the problem of optimization arrangement on mistuned blades.…”
Section: Introductionmentioning
confidence: 99%